1636. Risk of Latent Tuberculosis Reactivation in Patients Treated with Checkpoint Inhibitors Immunotherapy Compared to Other Anti-Cancer Therapies including Hematopoietic Cell Transplantation. (31st December 2020) - Malek, Alexandre; Chaftari, Patrick; dagher, Hiba; Hachem, Ray Y; Chaftari, Anne-Marie; Viola, George; Raad, Issam I; Raad, Issam I
Abstract: Background: The risk of latent tuberculosis infection (LTBI) reactivation in cancer patients during checkpoint inhibitor immunotherapy (CPI) remains largely unknown. We sought to evaluate LTBI therapy and outcomes between cancer patients receiving CPI versus conventional chemotherapy (CC) and hematopoietic cell transplantation (HCT) recipients. Methods: We conducted a retrospective cohort study of adult patients with LTBI (positive T-SPOT TB test) at MD Anderson Cancer Center between April 2016 and May 2020, who received CPI or combined with other conventional chemotherapy. Thereafter we compared each group to patients treated with other anti-cancer therapies including CC alone or HCT. Results: We identified 106 patients with LTBI, who were analyzed into 3 distinct groups: CPI (32 patients, 30%) CC alone (37 patients, 35%), and HCT (37 patients, 35% (7 autologous versus 30 allogeneic). The majority of patients in the CPI group (97%) had solid tumors compared to 54% in the CC group. Nivolumab was the most commonly used CPI agent in 13 patients (40%), followed by pembrolizumab 10 pts (31%). In the CPI group, 20 pts (62%) received LTBI therapy that included Isoniazid (INH), versus 18 patients (49%) in the HCT group and 16 patients (43%) in the CC group (p=0.26). Only 3 patients (CC group) had TB reactivations (8%; p=0.11). None of these 3 patients had received LTBI therapy or corticosteroids prior to the diagnosis. Immune-related adverse effect (IrAEs) were reported in 11 pts (34%) patients, and 9 (82%) of them received corticosteroids. Out of 20 of CPI patients whom received INH, 4 (20%) developed possible INH-induced liver toxicities leading to interruption of medication versus 1 (6%) patient which had mild hepatitis in CC group versus none of HCT patients (p=0.09). Conclusion: Our data suggest that latent tuberculosis reactivation remains rare, especially in the severely immunocompromised patients on CPI, CC and steroids. However, hepatotoxicity is relatively common in patients treated with CPI and INH. Therefore, caution and close laboratory and clinical monitoring is required to avoid significant hepatic injury and interruption of LTBI therapy and lifesaving oncological therapy. Disclosures: Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)